Toronto Math Forum
APM3462019 => APM346Lectures & Home Assignments => Home Assignment 3 => Topic started by: Wanying Zhang on January 28, 2019, 03:58:31 PM

I have difficulties obtaining the general solution of the equation $u_{tt}  c^2u_{xx} = 0$. From the online textbook Section2.3, it mentions $v = u_t +cu_x$, and it gets the result $v_t  cv_x = 0$ by chain rule. But when I expand $v_t  cv_x = 0$, I get an extra term $x'(t)$ when applies chain rule to $v_t$ because I think $u_{t}$ in $v$ can be two separated into to parts which are $u_t(t)$ and $u_t(x(t))$. Then applying chain rule, it becomes $v_t = u_{tt} + x'(t) +c(u_{xt} + x'(t))$ where the term $x'(t)$ can not be cancelled. I wonder where is the problem of my thought.

I have difficulties obtaining the general solution of the equation $u_{tt}  c^2u_{xx} = 0$. From the online textbook Section2.3, it mentions $v = u_t +cu_x$, and it gets the result $v_t  cv_x = 0$ by chain rule.
Not by a chain rule. Just from equation
But when I expand $v_t  cv_x = 0$, I get an extra term $x'(t)$ when applies chain rule to $v_t$ because I think $u_{t}$ in $v$ can be two separated into to parts which are $u_t(t)$ and $u_t(x(t))$. Then applying chain rule, it becomes $v_t = u_{tt} + x'(t) +c(u_{xt} + x'(t))$ where the term $x'(t)$ can not be cancelled. I wonder where is the problem of my thought.
Several days ago it was rewritten to make it more clear. Read online version